Photoswitchable Layer-by-Layer Coatings Based on Photochromic Polynorbornenes Bearing Spiropyran Side Groups - Campos, Paula P. [UNESP]; Dunne, Aishling; Delaney, Colm; Moloney, Cara; Moulton, Simon E.; Benito-Lopez, Fernando; Ferreira, Marystela; Diamond, Dermot; Florea, Larisa (American Chemical Society (ACS), 2018)
Herein, we present the synthesis of linear photochromic norbornene polymers bearing spiropyran side groups (poly(SP-R)) and their assembly into layer-by-layer (LbL) films on glass substrates when converted to poly(MC-R) under UV irradiation. The LbL films were composed of bilayers of poly(allylamine hydrochloride) (PAH) and poly(MC-R), forming (PAH/poly(MC-R))n coatings. The merocyanine (MC) form presents a significant absorption band in the visible spectral region, which allowed tracking of the LbL deposition process by UV-vis spectroscopy, which showed a linear increase of the characteristic MC absorbance band with increasing number of bilayers. The thickness and morphology of the (PAH/poly(MC-R))n films were characterized by ellipsometry and scanning electron microscopy, respectively, with a height of ∼27.5 nm for the first bilayer and an overall height of ∼165 nm for the (PAH/poly(MC-R))5 multilayer film. Prolonged white light irradiation (22 h) resulted in a gradual decrease of the MC band by 90.4 ± 2.9% relative to the baseline, indicating the potential application of these films as coatings for photocontrolled delivery systems.